Analisis Efisiensi Asuransi Jiwa Syariah di Indonesia dengan Pendekatan Stochastic Frontier Approach (SFA) - Rosyidatur Rohmah; Zubaidah Nasution (Universitas Islam Lamongan, 2022)
This study aims to analyze the efficiency level of Indonesian sharia insurance with a parametric stochastic frontier approach where the input is total assets and claims, and the output of this research is investment income. This study uses quantitative methods with secondary data in the form of shariah insurance Indonesia annual reports 2016-2020. The data analysis uses a regression test with the help of stochastic frontier approach (SFA). Based on the results of processing using stochastic frontier approach (SFA), Indonesian Sharia insurance's overall production efficiency level is known to be 0.8187 or 81.87%. Partially, Indonesian sharia insurance total assets and claims have an insignificant negative effect on investment income.